The value of repeated lumbar puncture to test for xanthochromia, in patients with clinical suspicion of subarachnoid haemorrhage, with CT-negative and initial traumatic tap. (4th July 2021) - China, Musa; Matloob, Samir A.; Grieve, Joan P.; Toma, Ahmed K.
Abstract: Objectives: For the diagnosis of subarachnoid haemorrhage (SAH), the presence of cerebrospinal fluid (CSF) xanthochromia is still considered the gold standard for patients with a thunderclap headache, in the absence of blood on brain CT scan. However, a traumatic lumbar puncture (LP) typically results in high concentrations of oxyhaemoglobin in CSF, impairing the detection of xanthochromia and preventing the reliable exclusion of SAH. In this context, the value of a repeat lumbar puncture has not yet been described. Materials and methods: A retrospective case series of suspected SAH patients, with a negative CT scan and initial traumatic LP, managed with a repeat LP to assess for CSF xanthochromia. Clinical notes, laboratory and imaging results were reviewed. Results: Between August 2011 and January 2020, 31 patients with suspected SAH were referred to our neurosurgical unit following negative CT and traumatic LP. A repeat LP was performed in 7 of the 31 patients, 2.4 days (±0.79 SD) after the first traumatic LP. CSF spectrophotometry analysis from repeated LP in all 7 patients was negative for xanthochromia. No adverse clinical events were recorded on average 18 months following discharge. Conclusion: A repeat LP performed following a traumatic tap can still yield xanthochromia-negative CSF, thereby, excluding SAH, avoiding unnecessary invasive angiography and overall promoting the safer management of these patients.